Effect of health belief model–based education on the prevention of pathological vaginal discharge: A pre-experimental study - Astriana, Willy; Zahra, Tamela; Wulandari, Putri (Lentera Perawat, 2025)
Background: Pathological vaginal discharge remains a prevalent reproductive health problem among young women and is often associated with inadequate preventive behaviors and limited health literacy. Educational interventions grounded in behavioral theory are needed to improve awareness and promote effective prevention strategies among female students. Objective: This study aimed to examine the effect of Health Belief Model–based education on the prevention of pathological vaginal discharge among female students. Methods: A quantitative pre-experimental study using a one-group pretest–posttest design was conducted among 60 female students at STIKes Al-Ma’arif Baturaja, selected through accidental sampling. The educational intervention was delivered using Health Belief Model–based leaflets focusing on perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, and cues to action. Data were collected before and after the intervention using validated questionnaires. Statistical analysis was performed using the Wilcoxon Signed Rank Test with SPSS software. Results: The findings demonstrated significant improvements in preventive behaviors and Health Belief Model components following the educational intervention. The Wilcoxon Signed Rank Test revealed a statistically significant difference between pretest and posttest scores (Z = −16.098; p = 0.003), indicating that Health Belief Model–based education effectively enhanced pathological vaginal discharge prevention among participants. Conclusion: Health Belief Model–based education significantly improves preventive behaviors related to pathological vaginal discharge among female students. Theory-driven educational interventions represent an effective approach for reproductive health promotion in academic settings.